Direct-site endovascular repair (DSER): A novel approach to vascular trauma. (November 2016) - Davidson, Anders J.; Neff, Lucas P.; DuBose, Joseph J.; Sampson, James B.; Abbot, Christopher M.; Williams, Timothy K.
Abstract : ABSTRACT: Peripheral vascular injuries carry significant risk for permanent functional impairment, limb loss, and death. Definitive correction of these injuries requires significant operative time and has traditionally been resource and skill set intensive. In the initial surgical treatment of the physiologically depleted trauma patient, faster techniques may prove more appropriate. Damage control techniques, including vascular shunting, rapidly restore distal flow but require additional vascular intervention and risk shunt thrombosis with prolonged use. To address these challenges, we present a technique, using an off-the-shelf endovascular device, for treatment of peripheral arterial injuries. Direct-site endovascular repair (DSER) is an open vascular surgical reconstruction technique using conventional endovascular stent grafts to create a "sutureless" anastomosis. We believe this technique to be a valuable adjunct to current repair options. The values of this technique are that it is (1) rapid, (2) of low technical complexity, (3) requires very little equipment, and (4) may offer extended durability in damage control scenarios. We describe three patients where this technique was used. In the first case, the technique was used to provide a temporary arterial shunt in a patient with a local infection and arterial disruption. In the second case, DSER was used for definitive repair of an injured artery after penetrating trauma. The third case involves DSER for definitive of both an artery and vein after penetrating trauma.